A novel mutation of X‐linked recessive deafness gene POU3F4 in a boy with congenital deafness. Issue 4 (1st July 2022) - Yu, Rong; Wang, Kai; Xiong, Yuanping; Jiang, Hongqun
Abstract: Purpose: To report an interstitial deletion of Xq21.1 in chromosome X in a boy with congenital deafness. Methods: The proband underwent a thorough physical examination and a detailed audiological and temporal bone computed tomography (CT) scan. Cochlear implantation was performed on the proband, and follow‐up was conducted. High throughput sequencing and copy number analysis was made of peripheral blood samples from the proband, family members, and control subjects. Results: Sensorineural hearing loss was present in the boy and temporal bone CT scan showed a bilateral incomplete partition type III anomaly (IP‐III). Q21.1 (79.40–83.32 Mb) of chromosome X in the proband had a copy number deletion with a fragment size of about 3.92 Mb. Categories of auditory performance scores and SIR scores of the cochlea in this child improved after surgery. Conclusion: Through the analysis of POU3F4, a novel mutation site with potentially pathogenic significance was found. Level of Evidence: 5. Abstract : The temporal bone computed tomography showed incomplete septal deformity of the bilateral cochlea (IP‐III) (Figure 2). Cochlear basal rotation was connected with the internal auditory canal. Bilateral vestibular semicircular canals were irregular in shape.